Using Remote Sensing and Geographic Information System (GIS) for Peak Discharge Estimating in Catchment of Way Ratai, Pesawaran District, Lampung Province. (June 2018) - Risky, Yanuar S; Wahyu, Nurbandi; Raden Ramadhani, Yudha A; Brada, Irmaning T; Artanti, Prisma Z; Rosyita, Alifiya; Wisudawan, Putra D; Sudaryatno,
Abstract: The catchment of Way Ratai is located in District of Pesawaran, Lampung Province. In the period of the last twenty years, there has occurred three times of flood disasters (1986, 1996, and 2017) in this catchment. Flood in March 2017 gave big impact for the Way Ratai village with the inundation was 1.0 – 1.7 meters. This study aims to estimate runoff coefficient (C) and peak discharge (Qp) using remote sensing and geographic information system (GIS). The research methodology includes cook method to estimate C value, rational method to estimate Qpr, and manning method to measure actual Qpm in field. Landsat 8 OLI imagery, digital elevation model (DEM) of SRTM, and rainfall data of 2014 – 2016 are used for estimate C and Qpr. Qpm is obtained from measure in the field. Qpr is compared with Qpm to analyze potential of flood. The results of this research are the catchment of Way Ratai has C: 0.615, Qpr: 543.45 m 3 /s, and Qpm: 194.10 m 3 /s. Qpm show river flow capacity is 543.45 m 3 /s. Its value is greater than Qpr rational method. It shows that the catchment of Way Ratai has potential of flood.